Analisis Historis Kemunculan dan Pelembagaan Ziyādat al-Thiqqah dalam Studi Hadis - Anshori, Muhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
This paper examines the origins of ziyâdat al-thiqqah and its institutionalization in hadith studies. The term of ziyâdat al-thiqqah was firstly initiated by al-Bukhârî in the middle age of the third century of Hijrah. At first, ziyâdat al-thiqqah was used to mean as adding sanad (chain of hadith narrators). But later, the term was also used in terms of matn (main text of hadith), which begins to be institutionalized in the 7th century of Hijriah. The goal of al-Bukhârî in setting up the term is to assert that the narrator should only receive the additional thiqqah narrators. This could also be a strategy of anticipation to minimize a counterfeiting of Prophet’s traditions. With the existence of ziyâdat al-thiqqah, it certainly brings influences on the narration of Hadith. This study finds that there are three implications of ziyâdat al-thiqqah in Hadith studies: the reconstruction of the theory of maqbûl, the acceptance of ziyâdat al-thiqqah as a form of variation, and the confirmation of the existence of al-isnâd al-‘âlî and al-isnâd al-nâzil.